Comparison between anterior cervical discectomy with fusion by polyetheretherketone cages and tricortical iliac-crest graft for the treatment of cervical prolapsed intervertebral disc (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Anterior cervical discectomy and fusion is effective surgical modality in the treatment of cervical prolapsed intervertebral disc, radiculopathy and myelopathy. Aims of our study is to evaluate fusion of cervical spine  by ICG with plating and PEEK cage with bone graft, also assess the donor site morbidity. Thirty patients (male 16; female 14) with mean age 46 ± 9.2 years and were distributed  into two treatment groups (PEEK cage group and ICG group). We assess the patients clinically for myelopathy and functional outcome by Nurick scale and Odom's criteria respectively and  neck and arm pain by Visual Analogue Scale (VAS). Eighteen patients were operated for single level discectomy and fusion by either ICG or PEEK cages and twelve patients for two levels. After surgery follow up was 2 years and better  postoperative score which was assessed by Nurick scale, Odoms criteria and VAS score. Total patients 14(93%)were graded excellent in the PEEK cage group compared to 13 patients (86%) in the ICG group.  Statistically it was not significant between two groups and p value was